CROSS-CULTURAL ANALYSIS OF PERSONAL NAMES MEANING 'WISHES' IN UZBEK AND GERMAN - Ziyodbek Abdullaev (Web of Journals Publishing, 2024)
The article is devoted to the comparative study of the anthroponyms of the Uzbek and German languages, in which personal names expressing desire are analyzed. In the anthroponymic system of the Uzbek language, the practice of naming a child with names expressing desire has been preserved, while in German, these motivated names have undergone various phonetic sound changes as a result of the blurring of their semantics, and historically, names expressing desire are not given as names today based on their semantics. They are given as names based on factors such as beautiful pronunciation and brevity.
Keywords: Uzbek, German, anthroponym, contrastive, motive, desire, desemantization